A REDEFINING CONCEPT OF EXPERT PHARMACY SERVICES FOR NEIGHBORHOOD DRUGSTORES - Ali Saad Abu-Dahash, Adel Saeed Saleh Alwadai, MAzyad Mufleh Alshaghatherah, ⁠Mazen Mohmmad Alharbi, Ozayyah Hamoud Mohmmed Alsharif, ⁠Muqbil Qubayl ALruwaytie, ⁠Fahad Sulaiman Alenazi, ⁠Adel Ail Alshahri,,; Ashwag Mohammed Alasmarei, Fahad Mohammed Abdu Hakami, ⁠Mazen Mohmmad Alharbi, Majed Mohammad Alotaibi, Abdulmajeed Mohammad Alotaibi, (Chelonian Research Foundation, 2022)
While there are many words and definitions used to characterize some parts of pharmacy practice and service delivery, none fully capture the scope of professional services provided by community pharmacies. The professional philosophy of pharmaceutical care or specific professional pharmacy services—particularly pharmaceutical services offered by pharmacists with an emphasis on drug safety, effectiveness, and health outcomes—are referenced in the majority of current pharmacy service definitions and nomenclature. Determining a professional pharmacy service within the framework of the community pharmacy model of service supply is thus the aim of this article. According to Donabedian's framework, the definition of a professional pharmacy service includes the concepts of organizational structure, process indicators, and outcome measures. It is defined as "an action or set of actions undertaken in or organized by a pharmacy, delivered by a pharmacist or other health practitioner, who applies their specialized health knowledge personally or via an intermediary, with a patient/client, population, or other health professional, to optimize the process of care, with the aim to improve health outcomes and the value of healthcare." The definition will help in many ways, such as recognizing the entire spectrum of services offered by community pharmacies and making it easier to identify signs of the implementation and sustainability of professional pharmacy services. A straightforward conceptual model that encompasses all of the services offered by community pharmacies is put forth. Keywords: Value of Healthcare, Medication, Pharmaceutical Care, Community Pharmacy Services, and Health Outcomes